Analysis of Surface Modification of GFRP and Influence on the Drilled Part Delamination - (:unkn) unknown (POLISH ACAD SCIENCES INST PHYSICS, 2017)
Glass fibre reinforced plastics are especially used in aviation industry, marine applications, automobile industry and wind power plants. The shape of the products to be manufactured from glass fibre reinforced plastics materials can be easily produced by using different primary methods [J.-M. Bertholet, Composite Materials, Springer, New York 2012, p. 54]. Assembly is necessary to create the final products which have been fabricated from glass fibre reinforced plastics. Components manufactured from glass fibre reinforced plastics are drilled with CNC, during assembling process. Several kinds of defects occur around the hole after drilling the materials. Presence of defects influences the quality of holes and of the products. The aim of this study is to make comparison between modified and unmodified composite materials, both of which are formed of 30% of glass fibres and 70% of epoxy resin, in terms of delamination factor. Influence of surface modification is evaluated to identify optimum drilling parameters by using Taguchi orthogonal L18 matrix. Surface condition, drill diameter, spindle speed and feed rate are changed as process parameters in the experiments. According to the study, feed rate and spindle speed are the most influential parameters and the drill tool surface condition does not show any general change.
Keywords: FIBER-REINFORCED PLASTICS; TAGUCHI METHOD; PROCESS PARAMETERS; HIGH-SPEED; COMPOSITE; OPTIMIZATION; NETWORK; FORCE